PENYELESAIAN SENGKETA HUKUM EKONOMI SYARIAH PERSPEKTIF TRADISI ISLAM KLASIK - Yuniartik Yuniartik (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This study discusses sharia economic law, where currently economic growth has developed greatly in accordance with the current era, so that people also find it difficult to solve Islamic economic problems. The focus of the problem in this study is how to solve economic problems in Islamic economic law from the perspective of the classical Islamic tradition? The purpose of this study is to find out how to solve economic problems using classical Islamic traditions. The type of research used is library research using a normative approach. And the results of this study found that in solving the problem of sharia economic disputes from the perspective of classical Islamic tradition, it can be reached in several ways including al-sulh (peace), tahkim (artbitration) and wilayat al qadha (judicial power).